1985
DOI: 10.1007/bf01347886
|View full text |Cite
|
Sign up to set email alerts
|

Giardiasis as a chronic disease

Abstract: In an effort to better describe the incidence and characteristics of chronic giardiasis in an urban private practice outpatient setting, we reviewed our experience of 65 cases. In the entire group, the mean duration of symptoms was 1.9 years. A history of foreign travel was described by 45%. No association with homosexuality was noted. Chronic giardiasis, defined as that population symptomatic for six months or longer, constituted 58% of the entire group (38 cases). For these patients the mean duration of symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Similar incidences of chronic giardiasis in male and female patients have been reported before [10], while in one study it was found that males were significantly more frequently affected by giardiasis than women [11]. However, the latter retrospective study did not distinguish between acute and chronic cases.…”
Section: Discussionsupporting
confidence: 63%
“…Similar incidences of chronic giardiasis in male and female patients have been reported before [10], while in one study it was found that males were significantly more frequently affected by giardiasis than women [11]. However, the latter retrospective study did not distinguish between acute and chronic cases.…”
Section: Discussionsupporting
confidence: 63%
“…In giardiosis, clinical manifestations represent the expression of host resistance and parasite virulence (Chester et al 1985). While structural studies only show alterations in the intestinal architecture (Ceballos et al 1995), in this series, we found changes in the intestinal structure as well as an increase in the GC population.…”
Section: Discussionmentioning
confidence: 46%
“…Symptoms have been reported to resolve in 60e70% of patients with chronic giardiasis when the parasites have been successfully eradicated. 29,30 Persistent abdominal symptoms in travellers, where Giardia may be an etiological agent, has been described, 31 but to our knowledge no long term follow-up or description of posttreatment symptomatic Giardia negative cases has been published.…”
Section: Discussionmentioning
confidence: 95%